Database Systems for Advanced Applications 15th International Conference, DASFAA 2010, Tsukuba, Japan, April 1-4, 2010, Proceedings, Part II - Kitagawa, Hiroyuki; Ishikawa, Yoshiharu; Li, Qing.; Watanabe, Chiemi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This two volume set LNCS 5981 and LNCS 5982 constitutes the refereed proceedings of the 15th International Conference on Database Systems for Advanced Applications, DASFAA 2010, held in Tsukuba, Japan, in April 2010. The 39 revised full papers and 16 revised short papers presented together with 3 invited keynote papers, 22 demonstration papers, 6 industrial papers, and 2 keynote talks were carefully reviewed and selected from 285 submissions. The papers of the first volume are organized in topical sections on P2P-based technologies, data mining technologies, XML search and matching, graphs, spatial databases, XML technologies, time series and streams, advanced data mining, query processing, Web, sensor networks and communications, information management, as well as communities and Web graphs. The second volume contains contributions related to trajectories and moving objects, skyline queries, privacy and security, data streams, similarity search and event processing, storage and advanced topics, industrial, demo papers, and tutorials and panels.
Trajectories and Moving Objects -- -tree: A Self-tuning Index of Moving Objects -- Privacy-Preserving Location Publishing under Road-Network Constraints -- Incremental Clustering for Trajectories -- NNCluster: An Efficient Clustering Algorithm for Road Network Trajectories -- Skyline Queries -- Dynamic Skyline Queries in Large Graphs -- Top-k Combinatorial Skyline Queries -- Extract Interesting Skyline Points in High Dimension -- Transitivity-Preserving Skylines for Partially Ordered Domains -- Finding the Most Desirable Skyline Objects -- Privacy and Security -- Multiple Sensitive Association Protection in the Outsourced Database -- A Semantic Information Loss Metric for Privacy Preserving Publication -- On t-Closeness with KL-Divergence and Semantic Privacy -- Competitive Privacy: Secure Analysis on Integrated Sequence Data -- Privacy-Preserving Publishing Data with Full Functional Dependencies -- Data Streams -- Scalable Splitting of Massive Data Streams -- Constraint-Aware Complex Event Pattern Detection over Streams -- Attribute Outlier Detection over Data Streams -- Similarity Search and Event Processing -- ISIS: A New Approach for Efficient Similarity Search in Sparse Databases -- Highly Scalable Multiprocessing Algorithms for Preference-Based Database Retrieval -- IO3: Interval-Based Out-of-Order Event Processing in Pervasive Computing -- Peer-to-Peer Similarity Search Based on M-Tree Indexing -- Storage and Advanced Topics -- Update Migration: An Efficient B+ Tree for Flash Storage -- Optimizing Write Performance for Read Optimized Databases -- Towards an Algebraic Framework for Querying Inductive Databases -- Efficient Aggregate Licenses Validation in DRM -- Industrial -- Development Procedure of the Cloud-Based Applications -- Rapid Development of Web Applications by Introducing Database Systems with Web APIs -- A General Maturity Model and Reference Architecture for SaaS Service -- Lazy View Maintenance for Social Networking Applications -- Birds Bring Flues? Mining Frequent and High Weighted Cliques from Birds Migration Networks -- Performance Improvement of OpenJPA by Query Dependency Analysis -- Chimera: Stream-Oriented XML Filtering/Querying Engine -- Demo -- Privacy and Anonymization as a Service: PASS -- Visual Evaluation of Outlier Detection Models -- ADERIS: Adaptively Integrating RDF Data from SPARQL Endpoints -- Outline of Community-Type Content Based on Wikipedia -- BISCAY: Extracting Riding Context from Bike Ride Data -- SERPWatcher: A SERP Mining Tool as a Novel Social Survey Method in Sociology -- Corona: Energy-Efficient Multi-query Processing in Wireless Sensor Networks -- Aquiba: An Energy-Efficient Mobile Sensing System for Collaborative Human Probes -- A Shoes-Integrated Sensing System for Context-Aware Human Probes -- DigestJoin: Expediting Joins on Solid-State Drives -- A Large Scale Key-Value Store Based on Range-Key Skip Graph and Its Applications -- Answering Range-Aggregate Queries over Objects Generating Data Streams -- Real-Time Log Analysis Using Hitachi uCosminexus Stream Data Platform -- Anddy: A System for Author Name Disambiguation in Digital Library -- A System for Keyword Search on Hybrid XML-Relational Databases Using XRjoin -- MediaMatrix: A Video Stream Retrieval System with Mechanisms for Mining Contexts of Query Examples -- Application Developments in Mashup Framework for Selective Browsing -- Retrieving System of Presentation Contents Based on User$1 (Bs Operations and Semantic Contexts -- Fuzzy Keyword Search on Spatial Data -- Adaptive Recommendation for Preferred Information and Browsing Action Based on Web-Browsing Behavior -- BIDEL: An XML-Based System for Effective Fast Change Detection of Genomic and Proteomic Data -- DISTRO: A System for Detecting Global Outliers from Distributed Data Streams with Privacy Protection -- Tutorials and Panels -- to Social Computing -- Mining Moving Object, Trajectory and Traffic Data -- Querying Large Graph Databases -- Future Directions of Innovative Integration between Multimedia Information Services and Ubiquitous Computing Technologies.s
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Information systems; Multimedia systems; Computer Science; Database Management; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Information Systems Applications (incl.Internet).; Multimedia Information Systems; User Interfaces and Human Computer Interaction